Property in the Third Universal Theory: The Green Book (The Libyan Application of This Theory) - مصطفی سلیمان , د. محمد محمد (Dirasat in Economics and Business, 1982)
This paper tried to survey and analyze several aspects regarding proparty as it is presented in the Green Book, therefore, it discussed and analysed, economic effectiveness justice, equality, and property. Taking the above four factors in consideration the question to ask was wether property should be owned in private or in common, or some sorts of combinations and restrictions that will characterize the property ownership differently. The paper suggested that the ownership of property should be treated differently, and therefore, four kinds of ownership may arise. 1. Property based on the wealth of society. 2. Land Property and its use. 3. Property necessary to liberate man's needs (e.g. House, Vehicle, Living me come). 4. Property of means of production (private property, socialist property). The paper concluded that applying the theory might take some time before we can reach the proper models that make the practice conceived with the theory in order to reach the ultimate goal of freedom and happiness.